Answers

2016-04-10T10:47:34+05:30
Given,
      x+7   -  9        
       5          x-2
=    (x+7)(x-2) -45
              5(x-2)
x²-2x+7x-14-45
            5x-10
x²+5x-59    -1
        5x-10

⇒ x²+5x-59 = 5x -10
⇒x²-59+10  = 0
⇒x² -49      =  0
⇒(x+7)(x-7) = 0    since (a² -b²) = (a+b)(a-b)
⇒x = +7, -7
0
brainliest please..........needed
The Brainliest Answer!
2016-04-10T11:22:20+05:30
 \frac{x+7}{5}  \frac{9}{x-2} = 1

 \frac{(x+7)(x-2) - 45}{5(x-2)} = 1

 \frac{x^{2} -2x +7x -14 -45}{5x-10} = 1

x² + 5x - 59 = 5x - 10

x² -49 = 0

x = 7 and -7
1 5 1